A Numerical Investigation on the Structure of the Zeros of Euler Polynomials - C. S. Ryoo; J. Y. Kang (Discrete Dynamics in Nature and Society)
Using numerical investigation, we observe the behavior of complex roots of the Euler polynomials En(x). By means of numerical experiments, we demonstrate a remarkably regular structure of the complex roots of the Euler polynomials En(x). Finally, we show the Julia set of Newton iteration function R(x)=x-En(x)/En′(x).